PENGEMBANGAN KOMPETENSI MAHASISWA MELALUI WORKSHOP BEBASIS POM QM FOR WINDOWS UNTUK ANALISIS QUALITY CONTROL - Suseno, Pangki; Junianto, Dwi; Mahariani, Yeni Roha; Suwignyo, Fahrul Afiyas (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2024)
Indonesia is currently in the era of Industry 4.0, which is an era of industrial digitalization that is the main reference in bringing major changes, including quality control. Quality has become one of the main variables of choice for companies in understanding and further developing quality to drive achievement in business. To develop this quality, human resources are required to have skills. The POM-QM program is a computer program that is used as an alternative application that can be used to assist decision making. The purpose of this service activity is to provide additional experience, skills and knowledge to students in interacting with technology in general and using POM-QM for Windows as a quality analysis tool. The implementation of the service was carried out on February 21, 2024, with lectures and exercises, as well as evaluation of the students' understanding before and after the training.. The implementation of the training included: installation of POM-QM for Windows software; software usage; and practice of quality analysis with POM-QM for Windows. The results of this PkM activity show that students have understood the installation and 57.9% of participants have understood the use of POM-QM for Windows software to solve quality problems and provide solutions. And from the evaluation results, it is known that the training is useful for students to solve quality problems quickly.